2019
DOI: 10.1177/2150132719878526
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge, Attitudes, and PrEP Prescribing Practices of Health Care Providers in Philadelphia, PA

Abstract: Introduction: Preexposure prophylaxis (PrEP) is an effective biomedical intervention that has the potential to dramatically decrease the incidence of HIV but remains an underutilized method of HIV prevention. The Philadelphia Department of Public Health administered an online survey to health care providers in the Philadelphia area with the aim of characterizing PrEP attitudes, knowledge, and prescribing practices. Methods: Online surveys were distributed to 1000 providers who were recruited through distributi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 17 publications
1
23
0
Order By: Relevance
“…Though less than half (43%) of survey respondents had prescribed PrEP in the previous 12 months, this proportion is greater than previously reported in the literature (4%-39%), 26 , 27 , 32 - 35 excluding one convenience sample of Philadelphia HIV/ID and non-HIV providers with an unusually high rate of PrEP prescription (77%). 36 Our finding may reflect the trend of increasing PrEP provision over time. 14 Provider surveys that included both PCPs and HIV/ID specialists have consistently reported that PCPs prescribed PrEP less often than HIV/ID specialists; 26 , 27 , 32 , 36 given that our results were primarily gathered from PCPs with very few responses from ID specialists (n = 3), this increased proportion of PrEP prescribers may be reflective of TN PCPs in general.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Though less than half (43%) of survey respondents had prescribed PrEP in the previous 12 months, this proportion is greater than previously reported in the literature (4%-39%), 26 , 27 , 32 - 35 excluding one convenience sample of Philadelphia HIV/ID and non-HIV providers with an unusually high rate of PrEP prescription (77%). 36 Our finding may reflect the trend of increasing PrEP provision over time. 14 Provider surveys that included both PCPs and HIV/ID specialists have consistently reported that PCPs prescribed PrEP less often than HIV/ID specialists; 26 , 27 , 32 , 36 given that our results were primarily gathered from PCPs with very few responses from ID specialists (n = 3), this increased proportion of PrEP prescribers may be reflective of TN PCPs in general.…”
Section: Discussionmentioning
confidence: 60%
“… 36 Our finding may reflect the trend of increasing PrEP provision over time. 14 Provider surveys that included both PCPs and HIV/ID specialists have consistently reported that PCPs prescribed PrEP less often than HIV/ID specialists; 26 , 27 , 32 , 36 given that our results were primarily gathered from PCPs with very few responses from ID specialists (n = 3), this increased proportion of PrEP prescribers may be reflective of TN PCPs in general.…”
Section: Discussionmentioning
confidence: 60%
“…The skipping rate for each question was satisfactory, ranging from 0% to 38.6% and the mean time to completion was almost 13 minutes. Because we gave no incentives to participants and we used a long questionnaire (39 questions), we consider our participation rate of 18.2% as very good, and in line with recent online surveys evaluating practice patterns by healthcare providers in which participation rates varied from 2% to 25% (18)(19)(20)(21)(22).…”
Section: Discussionmentioning
confidence: 87%
“…Because we gave no incentives to participants and we used a long questionnaire (39 questions), we consider our participation rate of 18.2% as very good, and in line with recent online surveys evaluating practice patterns by healthcare providers in which participation rates varied from 2% to 25%. (1822)…”
Section: Discussionmentioning
confidence: 99%
“…Because we gave no incentives to participants and we used a long questionnaire (39 questions), we consider our participation rate of 18.2% as very good, and in line with recent online surveys evaluating practice patterns by healthcare providers in which participation rates varied from 2% to 25%. (18)(19)(20)(21)(22) The outbreak of COVID-19 has drastically changed how outpatient care is delivered in health care practices. To decrease the risk of contamination for patients and health care workers, providers are deferring elective and preventive visits as well as non-emergency surgeries.…”
Section: Discussionmentioning
confidence: 99%